SOCIAL TOLERANCE IN DAILY LIFE BETWEEN MUSLIMS AND HINDUS IN PEMUTERAN VILLAGE, BALI - Tasya Zevila Amartha; Agus Machfud Fauzi (Jurnal Analisa Sosiologi, 2025)
This research aims to analyze the forms of social tolerance that exist in daily life between Muslims and Hindus in Pemuteran Village, Bali. Pemuteran Village is one of the areas in Bali that has religious diversity, where Muslims and Hindus coexist harmoniously. This research uses qualitative with a phenomenological approach, data collection is done through observation, in-depth interviews, and documentation methods to explore inter-religious social interactions in the village. The results of the research based on Social Construction theory show that Externalization is seen in mutual cooperation activities, interfaith participation in celebrating holidays, and respect for each other's traditions. Objectification is reflected through mutual recognition of tolerance as a social norm that regulates relations between people. Internalization, in the end, makes tolerance a collective consciousness that is inherited across generations. The results of this study show that tolerance in Pemuteran Village is a model of harmonious diversity, supported by open communication, local values that respect differences, and a shared awareness of the importance of harmony. Pemuteran Village proves that religious diversity can be a strength to create social harmony.